A deep view into the nucleus of the Sagittarius dwarf spheroidal galaxy: M54. Issue Volume 14:Issue S351(2019) (May 2019) - Alfaro-Cuello, M.; Kacharov, N.; Neumayer, N.; Mastrobuono-Battisti, A.; Lützgendorf, N.; Seth, Anil C.; Böker, T.; Kamann, S.; Leaman, R.; van de Ven, G.; Bianchini, P.; Watkins, L. L.; et al.
Abstract: Nuclear star clusters hosted by dwarf galaxies exhibit similar characteristics to high-mass, metal complex globular clusters. This type of globular clusters could, therefore, be former nuclei from accreted galaxies. M54 resides in the photometric center of the Sagittarius dwarf galaxy, at a distance where resolving stars is possible. M54 offers the opportunity to study a nucleus before the stripping of their host by the tidal field effects of the Milky Way. We use a MUSE data set to perform a detailed analysis of over 6600 stars. We characterize the stars by metallicity, age, and kinematics, identifying the presence of three stellar populations: a young metal-rich (YMR), an intermediate-age metal-rich (IMR), and an old metal-poor (OMP). The evidence suggests that the OMP population is the result of accretion of globular clusters in the center of the host, while the YMR population was born in-situ in the center of the OMP population.